Pendidikan Agama Islam untuk Sekolah Inklusi (Kajian Teori Pembelajaran Pendidikan Agama Islam di Sekolah Dasar) - Nuraini Nuraini (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2019)
Islamic Education Learning according to Muhaimin is "an effort to make students learn, need to learn, motivated to learn, willing to learn and interested in continually studying the religion of Islam, both to know how to practice religion and learn Islam as knowledge . Learning programs for students with developmental needs need to be made in stages, starting from annual programs, monthly programs, and daily programs. All contain intermediate goals (terminal objective), all of which contain the annual goals, and target behavior (target behavior). Daily programs are called learning units or learning designs. The design of learning is made or compiled based on information obtained from the results of the assessment, related to the level of ability and specific characteristics of each student concerned. as long as the teaching and learning activities take place, the teacher observes the behavior of the target that appears. classroom teachers who carry out teaching and learning activities together with partner teachers reflect on the activities of teaching and learning outcomes, reflection is more directed at student success both in terms of cognitive and social development.